Odysseus and his bed: from significant objects to thing theory in Homer - Grethlein, Jonas (The classical quarterly, 2019)
Things in Homer cannot complain about a lack of attention. Nearly forty years ago, Jasper Griffin, in response to the oralist emphasis on composition and formulaic language, drew our attention to the many significant objects populating the Iliad and the Odyssey. Nestor's cup, for example, is so heavy that other men have difficulties to lift it; the cup illustrates the eminence of its owner who rubbed shoulders with the far greater heroes of the past. As Griffin demonstrated, Homer deftly uses the significance of objects to enrich many scenes of his narrative. While the sceptre, symbol of the king's power, underscores the sorry figure cut by Agamemnon in Iliad Book 2, the washing places that Hector passes when he tries to escape Achilles generate a powerful tragic contrast to the battlefield chase in which he is now involved. Following Griffin's lead, scholars have closely examined things and their role in Homeric epic, notably their commemorative function: weapons and other objects have biographies and are therefore an important means of evoking the past besides song.
Gesehen am 22.07.2020